The Correlation between Confidence and Knowledge of Evidence-Based Practice among Occupational Therapy Students - Kate DeCleene Huber, OTD, MS, OTR; Alison Nichols, OTR, OTD; Kaila Bowman, OTS; Jessica Hershberger, OTS; Jessica Marquis, OTS; Taylor Murphy, OTS; Chelsea Sanders, OTS; Chanlar Pierce, OTS (Scholarworks @ WMU, 2015)
Evidence-based practice (EBP) is used throughout multiple health-care professions and includes the use of best research available, client preferences, and the practitioner's experience. Occupational therapy educational programs are required to incorporate EBP into their curriculum. A convenience sample of occupational therapy students from a private university completed a survey designed to measure students' knowledge and confidence in EBP. The survey consisted of the Knowledge of Research Evidence Competencies (K-REC) and the Evidence-Based Practice Confidence (EPIC) scale, as well as demographic questions. Of the respondents (n = 47), third-year students indicated higher confidence in the ability to utilize EBP and higher levels of knowledge related to EBP than second- or first-year students. The more didactic and clinical experience that the students had, the more knowledge related to EBP they had, which increased their confidence in the implementation of EBP. The knowledge and confidence that students gain of EBP within their educational training and clinical experiences can influence their future use and implementation of EBP as clinicians. Without this information, therapists will lack the confidence and ability to apply EBP principles in a changing and demanding health-care environment.